THE UKRAINIAN CONSERVATISM IDEOLOGY IN THE CONTEXT OF INFORMATIVE SOCIETY - Кошетар, У. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Political and religious bases of Ukrainian conservatism ideology as a factor of national identity preservation in informative society conditions is regarded in the article on the base of the analysis of Ukrainian conservative authors S.Tomashivsky and V.Zalozetsky works.